EP 9. GPi Deep Brain Stimulation for the treatment of status distonicus in tardive dystonia. Issue 9 (September 2016) - Trezza, A.; Landi, A.; Pirillo, D.; Antonini, A.; Sganzerla, E.P.
Abstract : Introduction: Dystonia is a movement disorder due to sustained muscle contractions that cause twisting and repetitive movements conditioning abnormal postures. Tardive dystonia generally follows long treatment with neuroleptics. An extreme condition called status distonicus may even be life threatening, determining spasm of axial musculature leading to respiratory or cardiac arrest. Bilateral pallidotomy provided significant benefit to dystonic symptoms in some patients; moreover, in recent years, pallidotomy has been replaced from pallidal DBS; pallidal DBS is particularly effective both in primitive generalized dystonia and in tardive dystonia consequent to neuroleptics. Objectives: To report DBS for the treatment of severe iatrogenic dystonia refractory to medical treatment. Patient and methods: A 19 years-old boy affected by severe behavior disorder was treated with neuroleptic drugs (haloperidole). After three years of treatment, appeared severe neck and axial dystonia with initial involvement of the extremities. The change in the pharmacological treatment led to an initial improvement, followed by a progressive and relentless worsening and loss of motor autonomy. The patient also experimented severe dysphagia and several episodes of ab-ingestis pneumonia. Anticholinergic and dopaminergic treatment failed to improve symptoms. The patient progressively felt in a generalized status distonicus. At admission, F-M DRS was 74. For this potentially threatening for life condition, he was candidated for bilateral GPi DBS. After stereotactic localization of ventro-mesial-posterior part of Gpi on volumetric isotropic T1 MRi coupled with Shaltenbrandt & Wahren atlas, bilateral DBS was performed in general sedation, with intraoperative neurophysiology. A couple of quadripolar electrodes were inserted and immediately connected with IPG (Activa RC Medtronic). Results: Stimulation started during postoperative day 2. After initial adjustment of the stimulation parameters we appreciated a clear reduction in the intensity and frequency of dystonic spasms, without surgical complication or adverse effects. At discharge the patient was able to walk without help, no dysphagia has been complained for and dystonic spasms were absent. Stimulation parameters were settled as following: left GPi 1- case positive, 2.0 V, 210 μs, 130 Hz; right GPi 9-case positive, 2.0 V, 210 μs, 130 Hz. At one year follow-up F-M DRS is 20. Conclusion: The role of DBS in secondary dystonia is still debated because of several failures; important factors in the surgical outcome are: the etiology of dystonia, the absence of skeletal deformity, younger age at surgery and shorter duration of disease. Another topic is the time of early efficacy of DBS, very varying among different reports, but generally considered in the span of weeks or months. Tardive dystonia, due to neuroleptic therapy, seems to be affected from DBS, better than other secondary forms. GPi DBS has also been described to be effective in the treatment of status distonicus and it is considered the treatment of choice in the acute management of this life-threatening condition. In this case we found a striking improvement in F-M DRS, since the first days, with prompt resolution of status distonicus. We suggest the indication to acute treatment with DBS in case of status distonicus in course of tardive dystonia.